Analisis nilai karakter peduli sosial pada kartun upin-ipin season 16 episode temanku susanti dalam menunjang pendidikan karakter peduli sosial pada siswa kelas III SD - Ahmad Laththuv Majid; Rukayah Rukayah; Sandra Bayu Kurniawan (Didaktika Dwija Indria, 2025)
This study aims to describe the value of social care characters contained in Upin-Ipin cartoons in supporting the implementation of social care character education in SD Negeri Jajar Surakarta. This research is qualitative descriptive research. The subject of the study was the cartoon Upin-Ipin season 16 episode "Temanku Susanti", a teacher and student of SD Negeri Jajar Surakarta. This study used data collection techniques in the form of observation, interviews, questionnaires, and documentation. Data analysis uses Miles & Huberman model analysis techniques, namely data reduction, data display, and conclusions. The result of this study is that the value of social care contained in the Upin-Ipin cartoon season 16 episode "Temanku Susanti" has values that can be applied by elementary school students. With the airing of Upin-Ipin cartoons, especially in the episode "Temanku Susanti" to students, it can support the education of students' social care characters.